MODEL STRUKTUR BANGUNAN RUMAH SEDERHANA DI DAERAH RAWAN LONGSOR GUNUNGPATI SEMARANG - Himawan Indarto; Hanggoro Tri Cahyo A. (Jurnal Teknik Sipil dan Perencanaan, 2015)
Every rainy season, residents in some residential locations prone to landslides in Gunungpati District of Semarang always concerned about the condition of their home and village roads are constantly shifting due to soil mass movement on the slopes. The movement of soil and foundation of the house that is not followed by the movement of the structure of the building houses on them, have very often result in damage to homes. For that we need a technical solution to ease the burden on the citizens. Technical solutions that will be in the form of a study of the system structure is simple house in accordance with the environmental conditions that are prone to landslides. In principle, the concept of making a safe home building structures to ground movement is to seek and make the whole elements of the foundation of the house and sloop, frame building (beams and columns), as well as the construction of the roof of the house, into a coherent whole and can not be separated on occurs when the ground motion (rigid body movement). The application of this concept, among others, is to create a connection that is strong enough and stiff among the various elements of the house, as well as the selection and implementation of appropriate material. The building houses designed using the principle of non-engineered construction and use of cheap materials and readily available, so that development can be done by local people without involving experts. With the existence of this study is expected to be made to the design of the structural model building simple houses to be built in areas prone to landslides.